SERVICE EXCELLENCE BAGI PERANGKAT DESA PADA KANTOR DESA TELUK DALAM - Santoso Santoso; Elly Rahayu; Rohminatin Rohminatin; Niki Fazira (Smart Education, 2024)
Abstract: The Prima (service excellence) is responsible for all services rendered to the public. The cuts are made from the fat of the soul, so the members on the first day they eat the fat. The first step is to lay down the first step of the treasury, which is covered with a large amount of money, and the public is left without a trace. The principle of service excellence is to provide the best service (service excellence) or attitude, attention, action, and appearance, (accountability). The PKM has been established in the membership of the members, and the staff is working on the pessary and the equipment. The staff is working on the pessary and the equipment is working on the pessary. first (service excellence) always paid. The local police station in the Department of Public Works, Jalan Besar, Department of Public Works, has 40 beds, the PKK Department of Public Works, and the LPM department have paid the fee and now the pessimists are waiting for the pessimists. The method is used to determine the method penyuluhan melalui kegiatan tatap muka from diskusi. It is important to note that the material used in the study is a different principle of education, the study of which is based on the principles of education that are applied to the public, and the technology that is used to develop the public education. The resulting cash flow is covered by the PKM team STMIK Royal, which is covered by the payment of the penalties for the entry of the members of the first batch of the cash flow, and the cash flow is covered by the cash flow, and the cash flow is covered by the cash flow.. Keyword: training, service, excellent; community, village Abstrak: Layanan Prima (service excellence) menjadi kewajiban yang harus dilakukan oleh penyelenggara pelayanan publik. Kesejahteraan masyarakat dapat diraih salah satunya dengan memberikan layanan prima kepada masyarakat. Layanan prima lahir dari kepedulian penyelenggara pelayanan publik terhadap kebutuhan dan harapan masyarakat. Terdapat beberapa prinsip yang berkaitan dengan pelayanan prima (service excellence) yaitu attitude, attantion,action, appearance (dan accountability.Tujuan dari kegiatan PkM ini adalah memberikan pengetahuan dan wawasan kepada peserta yang merupakan aparat Desa Teluk Dalam Kecamatan Teluk Dalam Kabupaten Asahan bagaimana memberikan layanan prima (service excellence) kepada masyarakat. Lokasi kegiatan di Kantor Desa Teluk Dalam Jalan Besar Teluk Dalam Dusun II dengan jumlah peserta 40 orang terdiri dari aparat desa, pengurus dan anggota tim PKK Desa Teluk Dalam, LPM serta beberapa masyarakat yang juga ikut menjadi peserta dalam kegiatan ini. Metode yang digunakan pendidikan masyarakat dengan metode penyuluhan melalui kegiatan tatap muka dan diskusi. Beberapa materi yang diberikan diantaranya prinsip-prinsip pelayanan prima, studi kasus pengaduan masyarakat tentang pelayanan publik dan penggunaan teknologi untuk meningkatkan pelayanan publik. Kata kunci: pelatihan,layanan,prima;masyarakat,desa